Three Way Decomposition for the Boltzmann Equation (Journal of Computational Mathematics, 2018)
The initial value problem for the spatially homogeneous Boltzmann equation is considered.A deterministic numerical scheme for this problem is developed by the use of the threeway decomposition of the unknown function as well as of the collision integral. On thisway, almost linear complexity of the algorithm is achieved. Some numerical examples arepresented.